Chemistry on your plate: coffee - Angeles-Boza, Alfredo Milton (2025)
The global consumption of coffee has experienced a notable increase in the last decade. The high global consumption of coffee is mainly attributed to its psycho-stimulant effects, influenced by genetic factors, and the perceived health benefits, although adverse effects are also recognized in some individuals. The complex chemistry of coffee, influenced by the bean, roasting, and preparation, impacts its flavor and properties. This article explores the chemistry of coffee, from the Arabica and Robusta species and their origin, to the processing methods (wet/dry) that modify the green bean. Transformations during roasting (Maillard reaction) are analyzed, as well as how roasting and extraction affect compounds like diterpenes and caffeine, and the sensory characteristics of coffee. Finally, the use of chemical techniques to determine the origin and purity of coffee is highlighted, underscoring the relevance of chemistry for a comprehensive understanding of this beverage.